The health education needed by the students concerning the detrimental effects of substance - Akın, Münevver (Journal of Dependence, 2000)
This study was carried out in 1995-1996 education term in order to determine the health education needed by the students concerning the detrimental effects of narcotic-stimulant substance use and to propose realistic precautions according to these results, with regard to the role of the nurse as health educator. Nine hundred eighty (980) students from. 3 high schools located in Bakırköy, Istanbul participated in this study. Simple randomization was used for student selection. The data were collected using a questionnaire sheet. The sheets were distributed after the students were informed about the questionnaire and the items and were immediately collected after they were answered. It was found that 33- 7% of the students have tried cigarette smoking and 31-2% of these continued smoking. The study revealed that 19-5% of the participants used alcoholic beverages in various intervals and the rate of alcohol use was higher in male students. Approximately 2.3% of the students reported to have tried sedative and tranquilizing drugs and 3-2% have tried cannabis use.